In Vitro Characterization of Gut Microbiota-Derived Commensal Strains: Selection of Parabacteroides distasonis Strains Alleviating TNBS-Induced Colitis in Mice - Cuffaro, Bernardo; Assohoun, Aka L W; Boutillier, Denise; Súkeníková, Lenka; Desramaut, Jérémy; Boudebbouze, Samira; Salomé-Desnoulez, Sophie; Hrdý, Jiří; Waligora-Dupriet, Anne-Judith; Maguin, Emmanuelle; Grangette, Corinne (Cells, 2020)
Alterations in the gut microbiota composition and diversity seem to play a role in the development of chronic diseases, including inflammatory bowel disease (IBD), leading to gut barrier disruption and induction of proinflammatory immune responses. This opens the door for the use of novel health-promoting bacteria. We selected five Parabacteroides distasonis strains isolated from human adult and neonates gut microbiota. We evaluated in vitro their immunomodulation capacities and their ability to reinforce the gut barrier and characterized in vivo their protective effects in an acute murine model of colitis. The in vitro beneficial activities were highly strain dependent: two strains exhibited a potent anti-inflammatory potential and restored the gut barrier while a third strain reinstated the epithelial barrier. While their survival to in vitro gastric conditions was variable, the levels of P. distasonis DNA were higher in the stools of bacteria-treated animals. The strains that were positively scored in vitro displayed a strong ability to rescue mice from colitis. We further showed that two strains primed dendritic cells to induce regulatory T lymphocytes from naïve CD4+ T cells. This study provides better insights on the functionality of commensal bacteria and crucial clues to design live biotherapeutics able to target inflammatory chronic diseases such as IBD.
Keywords: dospělí; Animals; Intestinal Mucosa; Trinitrobenzenesulfonic Acid; Female; feces; Feces; immune response; novorozenec; holobiont; Adult; ženské pohlaví; kolitida; DNA bakterií; Gastrointestinal Microbiome; IBD; Caco-2 buňky; DNA, Bacterial; Inflammatory Bowel Diseases; lidé; Infant, Newborn; Mice; Bacteroidetes; Mice, Inbred BALB C; myši; microbiota; colitis; T-Lymphocytes, Regulatory; modely nemocí na zvířatech; střevní mikroflóra; myši inbrední BALB C; functional screening; Colitis; kyselina trinitrobenzensulfonová; Disease Models, Animal; idiopatické střevní záněty; zvířata; probiotics; regulační T-lymfocyty; Caco-2 Cells; live biotherapeutic products (LBP); kvantitativní polymerázová řetězová reakce; střevní sliznice; Real-Time Polymerase Chain Reaction; Humans